High art - Carrier, David (Pennsylvania State Univ. Press, 1996)
The great poet Charles Baudelaire (1821-1867) was also an extremely influential art critic. High Art relates the philosophical issues posed by Baudelaire's art writing to the theory and practice of modernist and postmodernist painting. Baudelaire wrote in an age of transition, David Carrier argues, an era divided by the Revolution of 1848, the historical break that played for him a role now taken within modernism by the political revolts of 1968. Moving from the grand tradition of Delacroix to the images of modern life made by Constantin Guys, this movement from
Keywords: Baudelaire; Charles <1821-1867>; Baudelaire; Charles <1821-1867> - Critique et interprétation; Baudelaire; Charles <1821-1867> - Et l'art; Baudelaire; Charles; Delacroix; Eugène; Matisse; Henri; Modernisme (Art); Modernisme (art); Modernisme (cultuur); Oorsprong; Peinture - Philosophie; Schilderkunst; Malerei; Philosophie; Modernism (Art); Painting; Kunst; Moderne; Literatur; Ästhetik; Kunstkritik